Responsif Akan Pandangan Mengenai LGBT Berdasarkan Perspektif HAM, Agama, dan Hukum di Indonesia (International Forum of Researchers and Lecturers, 2023)
Sexual behaviour or actions that differ from generally accepted sexual norms in the LGBT community should not be considered something that should be taken for granted. This sexual behaviour or action arises because there are variations in individual sexual desires. Sexual orientation and habits refer to a person's desire to express their desire, love, emotions, and sexual activities towards individuals of the same gender, the opposite gender, or both. LGBT is an abbreviation for Lesbian, Gay, Bisexual, and Transgender, which refers to a group of individuals who have a sexual orientation or gender identity that is different from the majority. There are various views in society regarding LGBT, with some rejecting this variation in sexual behaviour while others openly accepting it. The debate regarding LGBT issues is increasingly intense and widespread, with various arguments related to human rights (HAM) and arguments based on religion. This research aims to investigate different views regarding LGBT issues in Indonesia, both from a religious and a human rights perspective.